Experiência de atividades para o cálculo diferencial e integral com o software geogebra - Amorim, Frank Victor (2011)
The discipline CDI I (Calculation Differential and Integral I) consists in the curricular structure of several areas as: Exact Sciences and of the Land; Technological; Biological and Humanistic. For there are difficulties with regard to CDI's Teaching Learning I, the present study has as thematic axis to seek to answer to the following matter: “How can the software utilization GeoGebra be used to a better Calculation I approach?”. Basing itself in this matter, the present work has the goal of elaborating activities sessions using the software GeoGebra concerning the main concepts of CDI I. Basing itself on resources offered by UFRN-Christmas (Federal University of Rio Grande do Norte - Native Campus), it elaborated activities sessions in the proposed investigative perspective. This work presents an activities sequence posts in sessions, in which the students work on couples or individually, to realize the functions initial concepts essence, iimits, derivatives and integral. After the accomplishment of a research accomplished close to the PROGRAD-UFRN (Pro- rectory of Graduation of the Federal University of Rio Grande do Norte), it chose a students' group who attended licenciatura in mathematics, for being, that course, one that they present íarger difficulties. These students were invited aleatoriamente take part herfrom encounters accomplished in the inverse turn in which the same studied. First it accomplished a Pilot, to be able to be analyzed better the proposal viability, as well as to accomplish improvements for the real. Like data collections instruments, they were used questionnaires answered by teachers and students, interviews accomplished informal after each encounter, reports performed by observant that were assisting in the experiment, sessions of answered activities and entregues, as well as the activities accomplished by the students in the Computer and entregues to the searching teacher. The sessions of applied activities helped to realize the improvements in the concepts comprehensions of CDI I by the students and teachers front to GeoGebra's Resources, mostly in the comprehension aspect propitiated by the visual and by means of the process of draging the illustrations in the Computer without occur losses in the structure of her constructions. It is worth point out that the software in himself has her limitations and that he does not do anything if the teacher does not have a good planning of his activities, as well as objective to are reached, clear and safe knowledge than is being taught and a software good knowledge. After the application of this product that the software was observed is of easy handling by students and teachers, it allows to the teacher who can detect better doubts and, still summarily, with regard to the student it noticed that they managed to relate better the graphic part with the algebraic.